Conserved neuronal-like and secretory programs define the spatial architecture of gastroenteropancreatic neuroendocrine tumors - Julie Karam; Samantha E. Hoffman; Amanda Garza; Dan Gui; Hannah I. Hoffman; Breanna M. Titchen; Yutaro Tanaka; Erica Pimenta; Theodora Pappa; Laura Valderrabano; Kevin Bi; Riaz Gillani; et al. (Journal of Clinical Investigation, 2026)
Gastroenteropancreatic neuroendocrine tumors (GEP-NETs) are clinically heterogeneous malignancies whose biology and microenvironmental organization remain poorly understood. Here, we integrated single-nucleus multiomic (snRNA-seq and snATAC-seq) and spatial transcriptomic profiling across 38 well-differentiated pancreatic (PanNET) and small-intestinal (siNET) tumors to define conserved malignant programs, their regulatory circuits, and spatial niches. We observed two conserved malignant cell programs spanning a continuous transcriptional spectrum: a neuronal-like program, and a secretory neuroendocrine program. Matched chromatin accessibility profiles uncovered distinct, tissue-specific regulatory networks, including MAX::MYC and MITF transcription factor binding motifs in siNETs versus ISL1 and TFAP4 in PanNETs, indicating organ-specific epigenetic control. Spatial transcriptomic analyses revealed that neuronal-like-high regions localized to densely cellular tumor areas with relative depletion of stromal infiltration, whereas secretory neuroendocrine-high regions occupied fibrovascular and stromal niches enriched for endothelial, fibroblast, and myeloid populations, and associated with TGFB1-ITGB1 , VEGFA-FLT1 , and LAMA2-ITGA1 signaling. Across both tumor types, the cNMF2 program was enriched in metastatic lesions and was enriched for pro-fibrotic and pro-angiogenic gene signatures. Thus, GEP-NETs are organized along a conserved neuronal-to-secretory axis defined by distinct epigenetic programs and spatially coupled to specific microenvironmental niches. This framework unifies NET heterogeneity across organ sites and identifies pathway-specific, microenvironment-linked vulnerabilities for therapeutic targeting.